Shear Strength Parameters of Sand Reinforced with Polypropylene Fiber - Aksoy, Suha; Edan, Omer Muhammad; Taher, Nichirvan Ramadhan (My University, 2021)
Improving the engineering properties of soils is one of the common necessity encountered in geotechnical engineering applications. This article investigates the effect of the addition of polypropylene fiber (PPF) on shear strength parameters of compacted sand. Different percentages of PPF (0.5%, 1.0% and 1.5%) by dry weight of the sand were added. Maximum dry density (MDD) and optimum moisture content (OMC) of sand alone and PPF-reinforced sand were measured by standard Proctor compaction test. Subsequently, shear box test was applied for sand and PPF-reinforced sand under three different normal stresses, samples were prepared under the condition of OMC and MDD. The results showed that when the percentage of PPF reaches 1%, the internal friction angle was at maximum value and cohesion is at the minimum value. With increasing percentage of PPF internal friction angle decreased and cohesion increased.
Keywords: Sand; Shear Box Test; Shear Strength Parameters; PPF; Standard Proctor Test